Ecopedagogy Learning Based on Bojonegoro Local Wisdom in Social Studies Subjects - Alfafa Ramadhani; Faridatul Lailiyah; Rifai; Armawati Hidayati (International Journal of Geography, Social, and Multicultural Education, 2026)
This study aims to analyze the implementation of the Bojonegoro local wisdom-based ecopedagogy approach in Social Studies (IPS) learning and its impact on students' environmental awareness. Indonesia has great potential in implementing local wisdom-based education to address issues of ecosystem damage such as deforestation and pollution. The research method used is a literature study (library research) with a thematic analysis approach to various relevant library sources related to ecopedagogy theory, local wisdom, and its implementation at the school level. The results of the study indicate that the integration of Bojonegoro local values, such as traditional irrigation systems, the utilization of Bengawan Solo mud sedimentation (the "Nggawan" system), the "Pladu" tradition, and conservation myths, can create a more contextual and meaningful IPS learning and can increase students' sense of ecological responsibility. The implementation of ecopedagogies also contributes to the achievement of the Sustainable Development Goals (SDGs), particularly in terms of quality education and climate change mitigation. However, this study identified a major challenge in the form of teachers' limited understanding of how to integrate local wisdom into established curricula. Therefore, intensive teacher training and the active involvement of local communities, such as farmers and traditional leaders, are needed to strengthen experiential learning materials. Overall, this article concludes that strengthening local wisdom-based education is a crucial strategy for developing a young generation that is environmentally sensitive and ready to become agents of change in building a sustainable society